Ethno-Survey of Traditional Use of Plants in Lolab Valley, Kashmir Himalaya - Mir, Tawseef Ahmad; Jan, Muatasim; Khare, Rakesh Kumar; Dhyani, Sandeep (Indian Forester, 2021)
Kashmir Himalaya lies in the north-western part of India. It is geographically a distinct belt, which is immensely rich in biological and cultural diversity. Medicinal plants form an important element of indigenous primary medical system of this region.An ethno-survey was conducted among the tribal communities of Lolab valley of Kashmir Himalaya to document the medicinal plants and associated traditional knowledge of its population using various interviews and group discussions. During the course of study a total of 70 plant species belonging to 68 genera and 42 families were reported to have medicinal importance. It was found that there is a very little information available about cultivation, sustainable harvesting and uses of these medicinal plant species. Hence there is a dire need to document these valuable plants and the traditional treasure associated with them.